2015
DOI: 10.1177/0969733014567024
|View full text |Cite
|
Sign up to set email alerts
|

Exploring nurses' personal dignity, global self-esteem and work satisfaction

Abstract: The relationships measured show that nurses' sense of dignity has commonalities with self-esteem, workplace satisfaction, spiritual commitment, and health status; the meaning of the findings has ramifications for the welfare of nurses internationally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 46 publications
2
24
0
1
Order By: Relevance
“…There is surprisingly little research on the self-esteem of nurses as a professional group (Sturm and Dellert 2016). The only relevant study that we can find using the Rosenberg Scale-our preferred measure-is by Peterson-Graziose et al 2013, which showed that poorer levels of self-esteem predicted attrition of American nurses from Associate Degree programmes.…”
Section: The Rosenberg Self-esteem Inventory (Rsei)mentioning
confidence: 97%
“…There is surprisingly little research on the self-esteem of nurses as a professional group (Sturm and Dellert 2016). The only relevant study that we can find using the Rosenberg Scale-our preferred measure-is by Peterson-Graziose et al 2013, which showed that poorer levels of self-esteem predicted attrition of American nurses from Associate Degree programmes.…”
Section: The Rosenberg Self-esteem Inventory (Rsei)mentioning
confidence: 97%
“…As we are going to see in the results, we can conduct some alternative actions oriented toward specific factors to experience a linkage to ourselves, others and our environment. Despite this holistic view, it is naturally more common to find literature studies that focus on restricted aspects of workplace spirituality such as performance, commitment, well-being, self-esteem, turnover, decision making, and so on [33][34][35][36][37][38][39][40].…”
Section: Reference Inner Life Purpose Communitymentioning
confidence: 99%
“…5,6 Hospital managers can also create environments conducive for the honouring of the professional dignity of the health team members. 7 When the professional autonomy of health professionals is ensured, their professional dignity is respected. 4 Although midwives have an autonomous practice, they also implement care that is prescribed by obstetricians in an environment that is created by hospital management.…”
Section: Introductionmentioning
confidence: 99%